2008
DOI: 10.1038/bmt.2008.61
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation for primary immunodeficiencies

Abstract: BMT is curative in almost 75% of children affected by severe primary immunodeficiencies (PIDs). Recently, the chance of cure has increased thanks to the availability of matched unrelated donors (MUDs). Nevertheless, besides the conventional indications to BMT (profound or absent T-cell function, profound or absent natural killer function, known syndromes with T-cell deficiencies), indications to BMT for PIDs affecting the quality of life or having an expectation of life that does not exceed the third-fourth de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…This study represents one of the largest single‐center studies of outcomes from the United States, representing diverse transplant strategies and demonstrating a favorable outcome in most cases. Survival has been the most consistently reported outcome for HSCT for SCID because data can be obtained from the SCETIDE and CIBMTR registries (European Stem Cell Transplantation for Immunodeficiencies, Center for International Blood and Marrow Transplant Research) (13, 34). Compared to the most recent reporting from these registries where overall survival was approximately 75%, our patient cohort had a higher survival rate of 86–88%.…”
Section: Discussionmentioning
confidence: 99%
“…This study represents one of the largest single‐center studies of outcomes from the United States, representing diverse transplant strategies and demonstrating a favorable outcome in most cases. Survival has been the most consistently reported outcome for HSCT for SCID because data can be obtained from the SCETIDE and CIBMTR registries (European Stem Cell Transplantation for Immunodeficiencies, Center for International Blood and Marrow Transplant Research) (13, 34). Compared to the most recent reporting from these registries where overall survival was approximately 75%, our patient cohort had a higher survival rate of 86–88%.…”
Section: Discussionmentioning
confidence: 99%
“…The database demonstrated that CGD was more common than perceived, and showed that significant morbidity and mortality were pervasive in CGD [17]. These facts served to accelerate bone marrow transplantation in CGD in the United States and in Europe [19,20]. In Europe, the seminal data collection on children with hyper-IgM syndrome revealed that severe liver diseases were more common than appreciated previously [21][22][23].…”
Section: Pid Patient Registriesmentioning
confidence: 98%
“…Hematopoietic stem cell transplantation (HSCT) is a therapeutic option for a number of non-malignant disorders, such as autoimmune disorders [1], inborn metabolic disorders [2], hemoglobinopathies [3], and immunodeficiency disorders (IDD) [4]. Autoimmune complications (AICs) after HSCT are still not well characterized but have multifactorial occurrence, such as autoimmune cytopenias (AICPs), autoimmune hepatitis (AIH), and autoimmune thyroid disease (AITD).…”
Section: Introductionmentioning
confidence: 99%